2012
DOI: 10.1097/pcc.0b013e318219266b
|View full text |Cite
|
Sign up to set email alerts
|

High mortality in patients with influenza A pH1N1 2009 admitted to a pediatric intensive care unit

Abstract: The mortality of children admitted to the pediatric intensive care unit with 2009 pH1N1 influenza was high (47%) in our population. Age <24 months, asthma, respiratory coinfection, need of mechanical ventilation, and treatment with inotropes were predictors of poorer outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 10 publications
2
23
0
1
Order By: Relevance
“…This is consistent with the finding that viral coinfection had little impact on morbidity and mortality in a sample consisting mostly of adult patients (79.3%) admitted to an intensive care unit (ICU) in Australia [11]. In a retrospective observational study with 142 critically ill children patients, showed that the co-infection of swine origin influenza A (H1N1) with respiratory syncytial virus (RSV) is a risk factor for respiratory failure and increased mortality [12]. None of these studies were mentioning the time frame of acquiring the second viral infection except, a recently published retrospective cohort study [13] reported that co-infection with H1N1 and another respiratory virus within 72 h of admission was not associated with worse clinical outcomes.…”
Section: Discussionsupporting
confidence: 69%
“…This is consistent with the finding that viral coinfection had little impact on morbidity and mortality in a sample consisting mostly of adult patients (79.3%) admitted to an intensive care unit (ICU) in Australia [11]. In a retrospective observational study with 142 critically ill children patients, showed that the co-infection of swine origin influenza A (H1N1) with respiratory syncytial virus (RSV) is a risk factor for respiratory failure and increased mortality [12]. None of these studies were mentioning the time frame of acquiring the second viral infection except, a recently published retrospective cohort study [13] reported that co-infection with H1N1 and another respiratory virus within 72 h of admission was not associated with worse clinical outcomes.…”
Section: Discussionsupporting
confidence: 69%
“…As would be expected, mortality risk is much higher when the infection follows a more severe course. In H1N1pdm09-infected children with severe illness admitted to ICUs, 81 % of whom underwent mechanical ventilation, death rates were 47 % [124]; many of these children had pre-existing illnesses such as asthma and congenital heart disease, and co-infection with RSV was found to be significantly associated with mortality.…”
Section: Burden Of Influenza In Childrenmentioning
confidence: 99%
“…Canada † [11] Turkey [55] Argentina [56] USA [57] France [58] Population studied (million habitants) Special Report also resulted in an increase in neonatal ICU admission indirectly or directly related to pandemic influenza A(H1N1)pdm09 in many jurisdictions [13]; however, this increase was not observed in Canada, where low birth weight admission in neonatal ICUs remained the same as during historical periods [101].…”
Section: Table 3 Main Children Characteristics In Intensive Care Unimentioning
confidence: 99%